Performance comparison of silicone and low-density polyethylene as passive samplers in a global monitoring network for aquatic organic contaminants. (1st June 2022) - Sobotka, Jaromír; Smedes, Foppe; Vrana, Branislav
Abstract: Contamination with hydrophobic organic compounds (HOCs) such as persistent organic pollutants negatively affects global water quality. Accurate and globally comparable monitoring data are required to understand better the HOCs distribution and environmental fate. We present the first results of a proof-of-concept global monitoring campaign, the Aquatic Global Passive Sampling initiative (AQUA-GAPS), performed between 2016 and 2020, for assessing trends of freely dissolved HOC concentrations in global surface waters. One of the pilot campaign aims was to compare performance characteristics of silicone (SSP) and low-density polyethylene (PE) sheets co-deployed in parallel under identical conditions, i.e. at the same site, using the same deployment design, and for an equal period. Individual exposures lasted between 36 and 400 days, and samples were collected from 22 freshwater and 40 marine locations. The sampler inter-comparability is based on a rationale of common underlying principles, i.e. HOC diffusion through a water boundary layer (WBL) and absorption by the polymer. In the integrative uptake phase, equal surface-specific uptake in both samplers was observed for HOCs with a molecular volume less than 300 Å 3 . For those HOCs, transport in the WBL controls the uptake as mass transfer in the polymer is over 20-times faster. In such a case, sampled HOC mass can be converted into aqueous concentrations using available models derived for WBL-controlled sampling using performance reference compounds. In contrast, for larger molecules, surface-specific uptake to PE was lower than to SSP. Diffusion in PE is slower than in SSP, and it is likely that for large molecules, diffusion in PE limits the transport from water to the sampler, complicating the interpretation. Although both samplers provided mostly well comparable results, we recommend, based on simpler practical handling, simpler data interpretation, and better availability of reliable polymer-water partition coefficients, silicone-based samplers for future operation in the worldwide monitoring programme. Graphical abstract: Image 1 Highlights: Feasibility of global aquatic monitoring of hydrophobic contaminants was demonstrated. Two co-deployed passive samplers showed similarities in chemical uptake. Water boundary layer controls the uptake of small molecules into both samplers. Large molecules showed slower uptake by polyethylene than by silicone. Silicone is recommended for passive sampling in a worldwide monitoring network.